Impact of point-of-care testing for respiratory viruses on antibiotic use in adults with exacerbation of airways disease. Issue 4 (October 2019) - Brendish, Nathan J.; Mills, Samuel; Ewings, Sean; Clark, Tristan W.
Highlights: Patients with exacerbation of airways disease had syndromic POCT for viruses. Antibiotics were stopped early in patients testing positive for viruses. There was no difference between influenza and non-influenza viruses. Syndromic POCT for viruses should be favoured over testing for influenza alone. Summary: Background: The ResPOC study demonstrated that syndromic molecular point-of-care testing (POCT) for respiratory viruses was associated with early discontinuation of unnecessary antibiotics compared to routine clinical care. Subgroup analysis suggests these changes occur predominantly in patients with exacerbation of airways disease. Use of molecular POCT for respiratory viruses is becoming widespread but there is a lack of evidence to inform the choice between multiplex syndromic panels versus POCT for influenza only. Materials/methods: We evaluated patients from the ResPOC study with exacerbation of asthma or COPD who were treated with antibiotics. The duration of antibiotics and proportion with early discontinuation were compared between patients testing positive and negative for viruses by POCT, and controls. Patients testing positive for viruses by POCT were compared according to virus types. Results: 118 patient with exacerbation of airways disease received antibiotics in the POCT group and 111 in the control group. In the POCT group 49/118 (42%) patients tested positive for viruses. Of those testing positive for viruses 17/49 (35%) had early discontinuation of antibiotics versus 9/69 (13%) testing negative and 7/111 (6%) of controls, p <0.0001. Of those positive for viruses by POCT 10/49 (20%) were positive for influenza, 21/49 (43%) for rhinovirus and 18/49 (37%) for other viruses. The proportion with early discontinuation of antibiotics was not different between the virus types ( p  = 0.34). Conclusions: This data suggests that syndromic molecular POCT for respiratory viruses should be favoured over POCT for influenza alone in adults with exacerbation of airways disease.